Multiple Cross-Species Transmission Events of Human Adenoviruses (HAdV) during Hominine Evolution - Hoppe, Eileen; Pauly, Maude; Gillespie, Thomas R; Akoua-Koffi, Chantal; Hohmann, Gottfried; Fruth, Barbara; Karhemere, Stomy; Madinda, Nadège F; Mugisha, Lawrence; Muyembe, Jean-Jacques; Todd, Angelique; Petrzelkova, Klara J; et al. (Molecular biology and evolution, 2015)
Human adenoviruses (HAdV; species HAdV-A to -G) are highly prevalent in the human population, and represent an important cause of morbidity and, to a lesser extent, mortality. Recent studies have identified close relatives of these viruses in African great apes, suggesting that some HAdV may be of zoonotic origin. We analyzed more than 800 fecal samples from wild African great apes and humans to further investigate the evolutionary history and zoonotic potential of hominine HAdV. HAdV-B and -E were frequently detected in wild gorillas (55%) and chimpanzees (25%), respectively. Bayesian ancestral host reconstruction under discrete diffusion models supported a gorilla and chimpanzee origin for these viral species. Host switches were relatively rare along HAdV evolution, with about ten events recorded in 4.5 My. Despite presumably rare direct contact between sympatric populations of the two species, transmission events from gorillas to chimpanzees were observed, suggesting that habitat and dietary overlap may lead to fecal-oral cross-hominine transmission of HAdV. Finally, we determined that two independent HAdV-B transmission events to humans occurred more than 100,000 years ago. We conclude that HAdV-B circulating in humans are of zoonotic origin and have probably affected global human health for most of our species lifetime.
Keywords: Hominidae; Zoonoses; adenovirové infekce; druhová specificita; zoonózy; Adenoviridae; molekulární evoluce; lidé; Animals; Evolution, Molecular; Adenoviridae Infections; Humans; zvířata; Species Specificity